Impact of COVID-19 pandemic on mental health and health behaviors in Swedish adolescents. Issue 1 (February 2022) - Chen, Yun; Osika, Walter; Henriksson, Göran; Dahlstrand, Johan; Friberg, Peter
Aims: There is an urgent need to explore the impact of the COVID-19 pandemic on adolescent mental health and health behaviours. To date, there are no such studies on Swedish adolescents. As COVID-19 emerged in the middle of our ongoing 2-year follow-up examination of the Study of Adolescence Resilience and Stress, we had the unique opportunity to use the corona outbreak as a 'natural experiment' to study the impact of COVID-19 on 15-year-old adolescents in Sweden. Methods: Adolescents (baseline age 13.6±0.4 years) were recruited from schools in western Sweden (during the COVID-19 outbreak schools were kept open for those under 16 years of age). The COVID-19 pandemic reached Sweden on 31 January 2020. A total of 1316 adolescents answered the 2-year follow-up survey before (unexposed to COVID-19 pandemic, controls) and 584 after 1 February 2020 (COVID19-exposed). Data on stress, psychosomatic symptoms, happiness, relationships with parents and peers, school and health behaviours were collected. Results: Adolescents reported higher levels of stress and psychosomatic symptoms and lower levels of happiness at follow-up compared to baseline. These changes occurred to a similar extent in both the control and COVID-19-exposed groups. Likewise, the COVID-19-exposed group showed no deterioration in peer relations or relations with parents versus controls. We did not find any significant differences between groups regarding sleep duration and physical activity.Conclusions: Swedish adolescents exposed to COVID-19 during most of 2020 showed no differences in longitudinal changes in mental health, relationships with parents and peers, and health behaviours compared to those not exposed to COVID-19 .